Robust Adaptive Control for a Class of Nonlinear Systems Using the Backstepping Method. (15th March 2013) - Zouari, Farouk; Saad, Kamel Ben; Benrejeb, Mohamed
This paper develops a robust adaptive control for a class of nonlinear systems using the backstepping method. The proposed robust adaptive control is a recursive method based on the Lyapunov synthesis approach. It ensures that, for any initial conditions, all the signals of the closed-loop system are regularly bounded and the tracking errors converge to zero. The results are illustrated with simulation examples.